LECTURERS’ PERCEPTIONS OF NEED FOR THE TEACHING OF CHARACTER DEVELOPMENT - Huyi Intan Sari (Proceedings Education and Language International Conference, 2017)
This study is aimed at investigating the lecturers’ perceptions of need for the teaching of character development for the fourth semester students at the English Literature Study Program of UNISSULA. There were two aspects being investigated; the perception of need for character development itself and those on character traits that the students were presumed to lack. A survey was done involving all 24 lecturers at the faculty as the respondents. A need analysis was resulted from the description of the survey results. Sets of questionnaire using Lickerts scale were distributed to the sample. The survey resulted the facts that most of the lecturers perceived that (1) teaching a subject means promoting both cognitive skills and social ones, (2) character development is as important as the English communicative competences, (3) character development needs to be paid more attention to at the department, (4) one of the best way in developing the students’ character is by integrating the teaching of character development into the syllabus. The lecturers also perceived that there were only seven character traits of the students requiring more attention to develop. The respondents tended to agree that the students of the department lacked the traits of self-discipline, perseverance, creativity, independence, curiosity, communicativeness, knowledge-ability, and responsibility. Keywords: perception, need, character development